EDUCATION AND TRAINING Perceived barriers to medical leadership training and methods to mitigate them in the undergraduate medical curriculum: A mixed-methods study of final-year medical students at two medical schools. Issue 3 (2020) - Omar, Adhnan; Shrestha, Ashish; Fernandes, Roland; Shah, Ankur
No abstract available